Optimal Embedding of Meyer Sets into Model Sets - Aujogue-, J (American Mathematical Society, 2016)
We give a constructive proof that a repetitive Meyer multiple set of Rd admits a smallest model multiple set containing it colorwise. © 2015 American Mathematical Society.